Endohedral metallocenophanes of rhodium and cobalt - Schaefer, Carsten; Scholz, Gerald; Gleiter, Rolf; Oeser, Thomas; Rominger, Frank (European journal of inorganic chemistry, 2005)
The synthesis of seven endohedral metallocenophanes of rhodium (7b, 8b) and cobalt (1d−h) with a cyclopentadienyl unit as one of the π-systems and a cyclobutadiene or cyclopentadienone unit as the second π-system is described, including the synthesis of the unsubstituted parent compound of the [CpCo(cbd)]-derived endohedral phanes, [3.3]-η5-(1,1',3,3')-cyclopentadienyl-η4-(cyclobutadienophane)co-balt(I) (1h). This compound could be obtained by deprotection of the corresponding trimethylsilyl-substituted endohedral phane 1g. The X-ray structures of 7b, 1e, 1g and 1h could be obtained. This paper compares their structural properties to the complexes reported in previous short communications. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2005)
Dedicated to Professor Paul von Ragué Schleyer on the occasion of his 75th birthday
Gesehen am 23.10.2020
Keywords: Festschrift